2017
DOI: 10.4314/ijbcs.v11i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial-guided isolation of constituents from <i>Senna alata </i>leaves with a particular reference against Multi-Drug-Resistant <i>Vibrio cholerae </i>and <i>Shigella flexneri</i>

Abstract: Senna alata is widely used in Cameroon for the treatment of several infections which include gonorrhoea, gastro-intestinal and skin diseases. Therefore, its leaves were investigated for antibacterial principles. Extraction of plant material was done with methanol, follow by partition with hexane. Separation and purification of compounds was done using a combination of chromatographic techniques. Isolated compounds were identified by means of spectroscopic methods and comparison with literature data. The antiba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…Taking into account the medical importance of the test microbial species, the result can be considered as promising for the development of new antimicrobial drugs. The antimicrobial activities of purified flavonoids corroborated with those of early reports against bacteria and fungi [ 5 , 11 , 26 28 ]. The antibacterial activity of the samples against V. cholerae and S. flexneri are particularly noteworthy since these strains were MDR clinical isolates which were resistant to commonly used drugs such as ampicillin, streptomycin, nalidixic acid, furazolidone and co-trimoxazole [ 16 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 84%
“…Taking into account the medical importance of the test microbial species, the result can be considered as promising for the development of new antimicrobial drugs. The antimicrobial activities of purified flavonoids corroborated with those of early reports against bacteria and fungi [ 5 , 11 , 26 28 ]. The antibacterial activity of the samples against V. cholerae and S. flexneri are particularly noteworthy since these strains were MDR clinical isolates which were resistant to commonly used drugs such as ampicillin, streptomycin, nalidixic acid, furazolidone and co-trimoxazole [ 16 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 84%
“…GC/MS characterization results on C. alata leaves showed that there were 7 compounds including 7 ((6Z)-7,11-dimethyl-3-methylidenedodeca-1,6,10-triene), 8 (4a,8-dimethyl-2-(prop-1-en-2-yl)-1,2,3,4,4a,5,6,8a-octahydronaphthalene), 9 (4,4,7a-trimethyl-5,6,7,7a-tetrahydro-1-benzofuran-2(4H)-one), 10 ( 3,7-dimethylocta-1,6-diene), 11 (hexadecanoic acid methyl ester), 12 (hexadecanoic acid), and 13 (octadecanoic acid methyl ester) [ 19 ]. Alkaloid compounds from C. alata leaves have also been identified, namely 14 ( adenine) [ 20 ], 15 (Chrysoeriol), 16 (quercetin), 17 (5,7,4′-trihydroflavanone), 18 ( kaempferol-3-O-beta-D-glucopyranosyl-(1→6)-beta-D-glucopyranoside), 19 ( n -dotriacontanol), 20 ( n -triacontanol), 21 (stearic acid), 22 palmitic acid [ 21 ], 23 diomestin [ 22 ], 24 (luteolin) [ 23 ], and 25 (1,3,5-trihydroxy-7-methylanthracene-9,10-dione) [ 24 ].…”
Section: Isolation Of Compoundsmentioning
confidence: 99%
“… [ 84 ] Seed Antioxidant DPPH radical scavenging and ferric reducing The antioxidant IC 50 values of seed in DPPH and ferric reducing were 4.01 ± 0.11 and 0.40 ± 0.21 μmol/mg, respectively. [ 23 ] Thrombolitic I n vitro thrombolytic activity The extract showed potent thrombolytic activity against negative control (water). [ 21 ] Anticancer Brine Shrimp Lethality by using shrimp larvae ( Artemia salina Leach) The cytotoxicity of ethanol extract of C. alata seed and gallic acid had LC 50 value 4.31 and 4.53 ppm, respectively.…”
Section: Pharmacological Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe emodin exhibited strong MIC activities (4 to 128 μg/ml). e marked activities could be linked to the anthraquinone and flavonoids compounds detected [59]. e antibacterial activity of chrysoeriol-7-O-(2″-O-beta-D-mannopyranosyl)-beta-Dallopyranoside,3-O-gentiobioside, quercetin, naringenin, and rhamnetin-3-O-(2″-O-beta-D-mannopyranosyl)-beta-D-allopyranoside isolated from chloroform, ethanol, petroleum ether, methanol, and aqueous leaves extract of S. alata, significantly inhibited the growth of B. subtilis, V. cholerae, Streptococcus sp., S. aureus, and E. coli.…”
Section: Pharmacological Activitiesmentioning
confidence: 97%